Profitability and Dividend Policy Affects Firm Value in The Infrastructure, Utility and Transportation Sector - Venina Cindy Kusumawati; Harijono Harijono (Universitas Pendidikan Ganesha, 2021)
Previous study uses six bank companies which are listed in Indonesia Stock Exchange as the object and using ROE in calculating profitability. The researcher suggests to using a variable other than ROE to calculate profitability, increasing the number of samples and using other sector such as infrastructure, utility and transportation sector as the object. Hence, this study aims to prove the effect of profitability and dividend policy on firm value in the infrastructure, utility and transportation sector. The data were obtained from the financial statements of company listed on Indonesian Stock Exchange. Firm value as a dependent variable were measured by price to book value, profitability and dividend policy as independent variable were measured by return on assets and dividend payout ratio. They were analyzed using Multiple Linear Regression with classical assumption test in Statistical Package for the Social Sciences program. The results indicated that profitability and dividend policy can affect firm value simultaneously, profitability has no effect on firm value while dividend policy can positively affect firm value.